Pelatihan dan Pengembangan E-commerce UMKM Produksi Keripik Desa Gunting Dalam Masa Pandemi Covid-19 - Izzalqurny, Tomy Rizky; Angelina, Beta; Yunitasari, Eva (Patria : Jurnal Pengabdian Kepada Masyarakat, 2023)
Gunting Village has good potential in the UMKM sector that is developed, one example is the UMKM production of chips. However, the COVID-19 pandemic has resulted in a decrease in market demand for chip products. This is caused by the decline in people's purchasing power, limited access to marketing, and the lack of innovative types of marketing that are carried out. E-commerce is considered capable of being an alternative marketing method. The purpose of this service program is to provide assistance and training to chips UMKM owners in Gunting Village regarding online product marketing in the midst of a pandemic. The method used is the Action Research method which involves the target community group, namely the owners of UMKM chips in Gunting Village. Through the results of the Focus Group Discussion and identification of problems carried out, the agreed solution was socialization, training and mentoring activities. The service team offers efforts to expand people's knowledge about how to modify their marketing in e-commerce. It is hoped that these UMKM actors will be able to expand the range of the products they market with e-commerce features during this pandemic. Activities carried out by the service team include socialization, training and assistance regarding how important and multifunctional the market place is, and social media. The result of this activity is that the UMKM community in Gunting Village has started marketing UMKM products with e-commerce, and the virtual promotion they are doing has also been formed.